The characteristics of natural open fractures in acoustic borehole image logs from the pre-salt Barra Velha formation, Santos Basin, Brazil. (February 2023) - Wennberg, O.P.; De Oliveira Ramalho, F.; Virgolino Mafia, M.; Lapponi, F.; Chandler, A.S.; Gomis Cartesio, L.E.; Hunt, David W.
Abstract: Natural open fractures have been reported in the Barra Velha Formation (BVE) in the pre-salt lacustrine carbonate reservoirs in the Santos Basin offshore Brazil. These fractures contribute to excess permeability i.e., well test permeability is significantly larger than core permeability or log derived permeability, and they are therefore important for the fluid flow in the reservoirs during production and injection. In this paper we summarize the characteristics of natural open fractures in acoustic borehole image logs (BHI) in 19 wells from the BVE reservoirs and discuss their distribution, occurrences and formation. The data quality is overall good and consistent so that results can be compared between wells. The P21 fracture intensity, which is fracture trace length per area (bore hole wall) was used, instead of Terzaghi corrected P10 fracture intensity which do not distinguish between minor and major fractures. Mean P21 fracture density shows a variation of 2 orders of magnitude between interpreted wells. Data binning was used in the analysis of P21 fracture intensity vs petrophysical parameters to reduce the effect of sampling volume being much smaller than the representative elementary volume (REV) of the fracture pattern. P21 fracture intensity shows a positive correlation with silica content, which varies in the carbonates, whereas the porosity is less important for fracture intensity. The occurrence of fractures is also associated with vug-fraction estimated from the acoustic BHIs. Fractures are also frequent in fault damage zones, above and below cavities. The main orientation of the fractures is NNW-SSE, that is in the same direction as the dominating fault trend, and this indicates a structural control on fracture formation. Natural open fractures are rare in high porosity rocks with a shrubby or grainy texture, and also in intervals with a conglomeratic appearance in the BHI image logs. Highlights: We characterise fractures and discuss their formation using acoustic BHI logs from pre-salt carbonates in the Santos Basin. Fracture density correlate with silica content, are frequent in fault damage zones and are associated with presence of vugs. The dominant fracture orientation is NNW-SSE i.e., in the same direction as the main fault trend in the area.